PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG VAGINITIS - Desy Ayu Wardani; Ridha Amelia Noor Aini; Ida Hayati (Jurnal Keperawatan Wiyata, 2022)
Background: Young women are susceptible to developing vaginitis if they do not maintain vaginal hygiene. Based on observations, it was found that young women experience vaginitis because they are still not exposed to information related to vaginitis and need to be given health education about vaginitis. Purpose: The purpose of this study was to determine the effect of health education using audio-visual media on adolescent girls' knowledge about vaginitis. Methods: This study is a quantitative study with pre- experimental one group pre-test and post-test. The population in this study were all grade VII students of SMPN 3 North Balikpapan. The research sample was selected using stratified random sampling, with a total sample size of 35 students consisting of classes A to K. Results: The study obtained Asymp values. Sig. (2-tailed) is 0,000 which means that it has an influence and there are 22 students who experience an increase in the value of knowledge after health education using audio visual media and there are 13 students who have constant scores on the pre-test and post-test. Conclusion: So it can be concluded that there is an effect of health education using audio-visual media on knowledge about vaginitis. Suggestion: Audio visual media can be done at school regularly.